2017
DOI: 10.1007/s00125-017-4294-3
|View full text |Cite
|
Sign up to set email alerts
|

Association of serum microRNAs with islet autoimmunity, disease progression and metabolic impairment in relatives at risk of type 1 diabetes

Abstract: Aims/hypothesis MicroRNAs (miRNAs) are key regulators of gene expression and novel biomarkers for many diseases. We investigated the hypothesis that serum levels of some miRNAs would be associated with islet autoimmunity and/or progression to type 1 diabetes. Methods We measured levels of 93 miRNAs most commonly detected in serum. This retrospective cohort study included 150 autoantibody-positive and 150 autoantibody-negative family-matched siblings enrolled in the TrialNet Pathway to Prevention Study. This … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
53
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 66 publications
(57 citation statements)
references
References 51 publications
(58 reference statements)
2
53
0
Order By: Relevance
“…In non-diabetic children (autoantibody positive) who participated in the T1D TrialNet Pathway to Prevention study, children with multiple autoantibodies and elevated miR-29a-3p, miR-21-3p, and miR-424-5p were more likely to progress to T1D within 2 years of follow-up [16]. In another cohort of non-diabetic children with islet autoantibodies, circulating miR-339-3p was elevated while miR-497-5p was decreased [17].…”
Section: Mirnas As Biomarkers In Type 1 Diabetes (T1d)mentioning
confidence: 99%
“…In non-diabetic children (autoantibody positive) who participated in the T1D TrialNet Pathway to Prevention study, children with multiple autoantibodies and elevated miR-29a-3p, miR-21-3p, and miR-424-5p were more likely to progress to T1D within 2 years of follow-up [16]. In another cohort of non-diabetic children with islet autoantibodies, circulating miR-339-3p was elevated while miR-497-5p was decreased [17].…”
Section: Mirnas As Biomarkers In Type 1 Diabetes (T1d)mentioning
confidence: 99%
“…Higher-dimension (genome-scale) assays were also included to identify data-driven features of disease progression. These included RNA-Seq of whole blood (30) and sorted B cell, CD4 + and CD8 + T cell, and monocyte subsets (32); immunophenotyping by flow cytometry (33); transcriptional response to T1D serum (22) assessed using Affymetrix microarrays; and serum miRNAs measured by quantitative PCR (qPCR) (24).…”
Section: Resultsmentioning
confidence: 99%
“…The transcriptional response to T1D serum assay was conducted as described previously (13). The miRNA assay was conducted using the Exiqon qPCR platform as described previously (24). The Treg transcript assay was performed using the NanoString platform as described previously (14,17), with samples for the Treg assay sorted concomitantly with the cell subset RNA-Seq sample set.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Of the many areas of potential interest and value, the study of microRNAs (miRNAs) has attracted attention, as they can be detected in serum. A recent study was reported of 93 such miRNAs in the serum of 150 children who were at high disease risk, as they had multiple DAA, and a similar number of low disease risk children without DAA [ 82 ]. It was found that 15 of these 93 miRNAs were higher or lower in the disease risk children, but that the disease’s sensitivity and specificity as a predictor was limited.…”
Section: Unknown: Features That Could Be Genetically Determinedmentioning
confidence: 99%